FeatSNP: An Interactive Database for Brain-Specific Epigenetic Annotation of Human SNPs - Ma, Chun-yu; Madden, Pamela; Gontarz, Paul; Wang, Ting; Zhang, Bo (Frontiers in Genetics, 2019)
FeatSNP is an online tool and a curated database for exploring 81 million common SNPs’ potential functional impact on the human brain. FeatSNP uses the brain transcriptomes of the human population to improve functional annotation of human SNPs by integrating transcription factor binding prediction, public eQTL information, and brain-specific epigenetic landscape, as well as information of Topologically Associating Domains(TADs). FeatSNP supports both single and batched SNP searching, and its unique interactive user interface enables users to explore the functional annotations and generate publication-quality visualization results. FeatSNP is freely available on the internet at FeatSNP.org with all major web browsers supported.